Polymerizing Pyrrole Coated Poly (l-lactic acid-co-ε-caprolactone) (PLCL) Conductive Nanofibrous Conduit Combined with Electric Stimulation for Long-Range Peripheral Nerve Regeneration - Song, Jialin; Sun, Binbin; Liu, Shen; Chen, Wei; Zhang, Yuanzheng; Wang, Chunyang; Mo, Xiumei; Che, Junyi; Ouyang, Yuanming; Yuan, Weien; Fan, Cunyi (Frontiers in Molecular Neuroscience, 2016)
Electrospinning and electric stimulation (ES) are both promising methods to support neurons adhesion and guide extension of neurons for nerve regeneration. Concurrently, all studies focus on either electrospinning for conduits material or ES in vitro study to accelerate nerve regeneration; few works on the combined use of these two strategies or ES in vivo study. Therefore, this study aimed to investigate the abilities of direct current ES through electrospinning conductive polymer composites composed of polypyrrole and Poly (l-lactic acid-co-ε-caprolactone) (PPY/PLCL) in peripheral nerve regeneration. PPY/PLCL composite conduits were synthesized by polymerizing pyrrole coated electrospun PLCL scaffolds. Morphologies and chemical compositions were characterized by scanning electron microscope and attenuated total reflection fourier transform infrared (ATR-FTIR). Rat pheochromyctoma (PC12) cells and dorsal root ganglia (DRG) cells cultured on PPY/PLCL scaffolds were stimulated with 100 mV/cm for 4 h per day. The median neurite length and cell viability were measured in PC-12 cells. The levels of brain-derived neurotrophic factor (BDNF), glial cell derived neurotrophic factor (GDNF) and neurotrophin-3 (NT-3) were analyzed in DRG cells. In rats, 15-mm gaps of sciatic nerves were bridged using an autograft, non-stimulated PPY/PLCL conduit and PPY/PLCL conduit stimulated with 100 mV potential, respectively. A 100 mV potential direct current ES was applied for 1h per day at 1, 3, 5, and 7 days post-implantation. The PPY/PLCL conduits with ES showed a similar performance compared with the autograft group, and significantly better than the non-stimulated PPY/PLCL conduit group. These promising results show that the PPY/PLCL conductive conduits combined use with ES has great potential for peripheral nerve regeneration.